A ‘Speed-Dating’ Model of Wound Care? Rapid, High-Volume Assessment of Patients With Diabetes in a Multidisciplinary Foot Wound Clinic - Sung, Jasper A.; Gurung, Seema; Lam, Teresa; Yusaf, Shehzi; Vicaretti, Mauro; Begg, Lindy; Cheung, N. Wah; Padmanabhan, Suja; Girgis, Christian M. (Experimental and Clinical Endocrinology & Diabetes, 2020)
Background Diabetes is a major risk factor for foot ulceration and leg amputation, but the effect of intensive glycaemic control on wound healing is unknown. While an interdisciplinary approach has been shown to be important in the management of diabetic foot ulcer (DFU), there is no standardised definition of such an interdisciplinary team.Objective To investigate the role of an opportunistic, rapid-access, inter-disciplinary model of diabetes care at a foot wound clinic.Methods A retrospective case-control study of patients with DFUs attending a diabetes foot wound clinic over a 6-month period. Outcomes in patients who were seen by a rapid-access interdisciplinary team (RAIT) consisting of an endocrinologist, diabetes educator and dietician during the standard wound care those who were not seen by this team were compared.Results Fifty-five patients were seen by the RAIT and 64 control patients were not seen by this team during their attendance of a diabetes foot wound clinic. Patients in the intervention group had non-significantly higher baseline HbA1c and a significantly larger proportion were active cigarette smokers. Both groups achieved comparable reduction in the total number of DFUs per patient (p=0.971). Patients in the intervention group had a 60.1% reduction in wound size compared to 52.4% reduction in control group (p=0.526).Conclusion Our study shows that the use of a rapid-access interdisciplinary team to assess and manage patients’ diabetes in a foot wound clinic is feasible. Patients with higher-risk diabetes foot wounds exposed to RAIT had comparable wound healing outcomes to lower risk patients.
Keywords: diabetes autoimmunity; peripheral arterial disease cardiovascular incidences; neuropathy